Exploring the perceptions of foreign language Spanish educators of hybrid teaching training - Capanegra, Ana (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
The present study aims at the implementation of the American Council on the Teaching of Foreign Languages (ACTFL) advancements on the role of educators in technology-enhanced language learning. It reviewed perceptions of foreign language instructors and teaching assistants regarding the quality of the training for the teaching of hybrid courses at an urban university in the Midwest. The incorporation of the pedagogical aspect to the online component helped them with class dynamics that fostered learning and retention. Additionally, they formed a learning community to share their experiences of pedagogical issues.